Faktor-faktor yang Mempengaruhi Risiko Pendapatan Usahatani Padi Sawah Tadah Hujan (Studi Kasus di Kelurahan Boriappaka Kecamatan Bungoro Kabupaten Pangkep) - Syahrianti Syahrianti; Arifin Arifin; Mohammad Anwar Sadat (Jurnal Agribis, 2021)
Farming risk arises because of conditions of uncertainty. The purpose of this study was to determine the factors that influence the risk of income from rainfed lowland rice farming ini Boriappaka Village, Bungoro District, Pangkep Regency. The population in this study was taken randomly or Simple Random Sampling on rainfed lowland rice farmers, in determining the sample will be taken a sample of 25 respondents who are angaged in rainfed rice farming. The study uses multiple regression data analysis to determine the factors that influence the risk of income rainfed lowland rice farming in Boriappaka Village, Bungoro District, Pangkep Regency. The result of this study will affect the actual production and income of ferlilizers and pesticides.